Tradition and Modernity within Islamic Civilization - Pakeeza, Shahzadi; Iftikhar, Nosheen (Journal of Islamic and Religious Studies, 2016)
Colonialism has impacted on Islamic Law as well as Islamic civilization. Islam has a dissonant relationship with modernity in that it agrees with central aspects of this epochal phenomenon and parts ways with others. The compatibility issues were raised by the Muslim thinkers. Many Muslim scholars have contributed to give an original understanding of message of Islam detached from sectarian influences. Traditions are considered to be the vehicle for the transference of factors to modernity with a strong role in determining power and culture of a civilization. Thus, they pave the way for the power tools of a civilization. The theories of Muslim scholars from Asia and Egypt are discussed to elaborate the Muslim understanding of facing the challenges of modernity. The contemporary scholars’ views are also added with an analysis of their observation on compatibility of Islam with modern era challenges and the criticism on it due to their modernity conception.